The Making of Englishmen Debates on National Identity 1550-1650 - Larkin, Hilary (Studies in the History of Political Thought, 2013)
Making the Englishmen offers an account of how national identities were construed and contested in the post-Reformation public sphere 1550-1650. Readership: For historians of ideas primarily - it is in the history of political thought series. Also aimed at historians of the phenomenon of nationalism/national identity. Historians of early-modern England and Britain. Cultural historians.